Endobronchial coil treatment in severe emphysema patients with alpha-1 antitrypsin deficiency - Perotin, Jeanne Marie (Int J Chron Obstruct Pulmon Dis, 2018)
Endobronchial coil treatment (ECT) is a minimally invasive procedure developed for palliative care of patients with severe emphysema. ECT has demonstrated a decrease in hyperinflation, an improvement in quality of life, and an acceptable safety profile in randomized controlled trials (RCTs). Because alpha-1 antitrypsin deficiency (AATD) is a classical exclusion criterion in RCTs, there is no available data for ECT in AATD. In this post hoc analysis of the REVOLENS study (Réduction volumique endobronchique par spirales; ClinicalTrials.gov Identifier: NCT01822795), a multicenter 1:1 RCT which compared bilateral ECT with usual care in severe emphysema, we analyzed the efficacy and safety results at 1 year in six patients with AATD (five males, one female; mean age: 52±9 years) who underwent ECT. A significant decrease in hyperinflation (0.35 L decrease in residual volume [RV]) was observed in four out of six patients at 6 months and three out of six patients at 12 months, and an improvement in quality of life (improvement of 4 points in the St George’s Respiratory Questionnaire [SGRQ]) was observed in four out of six patients at both 6 and 12 months. Efficacy results at 6 and 12 months from the six AATD patients were compared with 84 non-AATD patients who underwent ECT, and no statistically significant differences were found for FEV(1), RV, 6MWT score and SGRQ score. Respiratory-related serious adverse event was limited to pneumonia in one AATD patient at 1 year post-ECT. This post hoc study suggests that AATD patients may have similar efficacy and safety outcomes at 1 year as non-AATD patients. Because of the paucity of available data, appropriately powered studies are needed to determine the effects of ECT in AATD.